2005
DOI: 10.1093/humrep/deh644
|View full text |Cite
|
Sign up to set email alerts
|

Day 14 maternal serum progesterone levels predict pregnancy outcome in IVF/ICSI treatment cycles: a prospective study

Abstract: In spite of exogenous progesterone supplementation, serum progesterone levels, from as early as 4 weeks gestation (day 14 post-oocyte retrieval) were significantly elevated and predicted women destined to have viable intra-uterine pregnancies. These high levels are suggestive that endogenous progesterone is already sufficient in viable pregnancies and that exogenous progesterone administration will not rescue a pregnancy destined to result in a miscarriage. Single serum progesterone measurement could be a usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Progesterone is involved in endometrial maturation and high levels of this hormone allow for complete transformation of the endometrium [47]. Progesterone levels in the luteal phase are positively correlated with the chance of successful conception [48,49] and negatively correlated with uterine arterial pulsatility, which was found to be associated with recurrent pregnancy loss [50]. In women undergoing embryo transfer, live birth rates were greater for those receiving progesterone, compared with those who did not take progesterone [51].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone is involved in endometrial maturation and high levels of this hormone allow for complete transformation of the endometrium [47]. Progesterone levels in the luteal phase are positively correlated with the chance of successful conception [48,49] and negatively correlated with uterine arterial pulsatility, which was found to be associated with recurrent pregnancy loss [50]. In women undergoing embryo transfer, live birth rates were greater for those receiving progesterone, compared with those who did not take progesterone [51].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the single progesterone assay on day 14 postoocyte retrieval was significantly high in women with on-going pregnancies compared to women with an abnormal pregnancy. Ioannidis and colleagues concluded that single serum progesterone measurement could be a useful indicator of pregnancy outcome in women undergoing IVF/ICSI treatment (Ioannidis et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…No correlation between increased mid-luteal serum P levels and high pregnancy rate in women undergoing COH was observed. In contrast, Ioannidis et al (16) have suggested that mid-luteal serum P measurement may be a useful indicator of pregnancy, with high sensitivity and specificity. Some investigators have reported higher preimplantation levels of P in pregnant women, whereas lower levels were found to be associated with abnormal pregnancies (17)(18)(19).…”
mentioning
confidence: 94%